Osseous Sarcoidosis with a Solitary Lytic Skull Lesion: A Case Report - Thirunavukarasu, Vignaraja; Thirunavukarasu, Caitlin; Willis, Timothy; Tsahtsarlis, Antonio (Journal of Neurological Surgery Reports, 2019)
Bone sarcoidosis is an uncommon manifestation of the multisystemic disease with skull involvement being rare. We present the case of a 32-year-old female who was referred by her General Practitioner with a left calvarial lesion on a background of previous unilateral 7th nerve palsy and diabetes mellitus. Images demonstrated a left frontoparietal calvarial osteolytic lesion. She underwent resection by the neurosurgical team with histopathological study revealing noncaseating granulomas, consistent with sarcoidosis. Given absence of other systemic features of sarcoidosis, she did not undergo systemic treatment.
Keywords: osseous sarcoidosis; neurosurgery; histopathological diagnosis; skull sarcoid